COMBINED TREATMENT OF LOCALLY-ADVANCED BLADDER CANCER - I. V. Chernyshev; Y. V. Samsonov; D. V. Perepechin; A. M. Ulbashev (Исследования и практика в медицине)
Bladder cancer (BC) is an important clinical and scientific challenge. In 2013, in Russia, the absolute number of patients with first-ever diagnosis of bladder cancer was 12 992 people. There is an increasing proportion of detection of bladder cancer stage I–II disease patterns: 2003–50.8% in 2013–69.6%, while the number of newly diagnosed patients in III and IV clinical stages remains at 30%. The proportion of individuals who completed the treatment of the number of newly diagnosed patients with bladder cancer in 2013, was as follows: only surgical method — 65.4%, 33.5% combined. Purpose. Improvement of the results of treatment of patients with locally advanced bladder cancer. Materials and methods. The main treatment for muscle-invasive bladder cancer is radical cystectomy. In the combined treatment of bladder cancer chemotherapy is the component that systemic exposure to the tumor, the way of regional and distant metastases. The study included 132 patients with locally advanced bladder cancer who were treated for 2005–2013, divided into four groups: NACT + CE — 27 people (20.5%), CE + ACT — 21 (15.9%), NACT + CE + ACT — 21 (15.9%) only CE — 63 (47.7%). An important component of treatment has been the use of platinum (cisplatin or carboplatin) in Schemes M–VAC and GP. An objective response is possible in 44.7%, and the stabilization process in 40.4% of patients.Results. The clinical effect is evaluated in all patients. In the group of NACT 21% of patients survived for more than 4 years, but did not survive the 5‑year mark. In the group of CE + ACT the indicator achieved only 3‑year survival rate, which amounted to 43%. In the group of CE — none of the patients did not live up to 3 years, with 2‑year survival rate was 30%. In the group of ACT + NCT + CE 3 patients (15%) were alive at the time, passed the threshold of the 5‑year survival rate, there is no progression of cancer.Conclusion. Combined treatment mode NACT + CE + ACT can achieve significantly longer time to tumor progression and better overall survival; the reverse side is to increase the frequency of postoperative complications.